Application Coaching Support in Efforts to Regulate Diet and Fluid Restriction in Patients with Chronic Kidney Disease - Susanti Susanti; Difran Nobel Bistara (UNUSA Press, 2022)
Proper diet and fluid restriction are very important things to note, because intake Excessive fluids can worsen the condition of patients with kidney disease. Although patients already understand that failure to limit fluids can be fatal, about 50% of patients with Chronic Kidney Disease (CKD) do not adhere to the recommended dietary and fluid restriction diet. Management of chronic kidney disease with diet and fluid restriction can be done by nurses by providing coaching support. The method of implementing community service which is carried out through the provision of coaching support is by providing health education gradually and continuously by paying attention to the problems experienced by Chronic Kidney Disease (CKD) sufferers so that awareness of the disease is achieved and the end result is an improvement in the behavior of the sufferer. Participants in this activity are all CKD patients who carry out routine checks at the Internal Medicine Poly Hospital of Adi Husada Surabaya from April 2021 to June 2021. Meetings with participants are followed up at the participants' homes for intervention. The behavior of the fiber was observed before and after the intervention. The results obtained before the intervention was given, most of the participants had poor behavior as many as 11 people (55%) and after being given coaching support most of the 12 people (60%) had good behavior in diet and fluid restrictions. Based on these data, it can be seen by using the Wilcoxon Signed Rank Test statistical test, the behavioral value p value = 0.001 so there is an effect of providing coaching support on the behavior of diet regulation and fluid restriction. Providing coaching support can be one of the therapies for CKD sufferers in maintaining stable kidney function so that the patient's quality of life becomes better